The Greek myths, part I myth as fiction, history and ritual - Highet, Gilbert 1906-1978.; Barnes, John. (Chicago Encyclopedia Britannica Film Corp., 1971)
Uses dramatizations and animation to present Greek myths as primitive fiction, primitive history, primitive science, primitive psychology, early attempts to understand the origins of the universe, and as a basis for drama and religious inquiry.
VCD.
Serial no. PW08FY092199
Exclusive distributor: High Access Line Phils. Corp., Mandaluyong City.
Keywords: Mythology, Greek; Greek fiction -- History and criticism